REFUGEE AND EXTRADITION: COULD A REFUGEE BE EXTRADITED? - Parthiana, I Wayan (UI Scholars Hub, 2010)
Refugees are people who are basically forced to leave their homes because of security threats and threats to safety of body and soul, go to another place which he considered safer. There are refugees who fled within the territory of his own country but it is not uncommon that they cross state boundaries. But among so many refugees who cross national borders, sometimes there are some who (allegedly) as a criminal in their home country or in third countries. He used the privileged of becoming refugees in order to avoid criminal charges of the country that has jurisdiction over his crimes. These type of refugees or called illegal refugees, could be extradited as long as they met the principles and rules of law on extradition. While the legal refugees could not be extradited because they are not criminals except if recently it was discovered that they are criminals.